KAJIAN Anacusis (Penderita Tunarungu) PADA PEMBELAJAR DALAM PEROLEHAN BAHASA INGGRIS SEBAGAI BAHASA ASING - Khoirul Huda (PENTAS : Pendidikan Bahasa dan Sastra Indonesia, 2017)
Language is the main customs of communication for human being life. Anacusis is total loss or absence of the ability to perceive sound as such. It also known as deafness. Because of brain plasticity changes during early childhood, children who have not acquired a first language in the early years might never be completely fluent in any language. An alternative to speech-exclusive approaches to language acquisition for deaf children exists in the use of sign languages such as Sistem Isyarat Bahasa Indonesia (SIBI), where acquiring a sign language is subject to the same time constraints of spoken language development. This study is intended to find out the answer to the following questions : (1) Which are educational method and communication method used in learning English for Anacusis learners, (2) How well do Anacusis learners acquire English as a foreign language, (3) What problems do Anacusis learners face in learning English. A descriptive qualitative research design was used in this study. The data of this study were observation result. The source of data in this study was drawn by using simple stratification sampling technique. The number of data used as discussion material of this study was 3 data. Documentary or content analysis was used to collect the data. The data were collected from interview result, observation checklist and test result by identifying the contents. The data are analyzed by describe the result of collected data, and then compare the finding with certain statement from some scientist and recently researchers. The result of the study showed that Anacusis learners able to acquire English as a foreign language although need a little harder effort compared with non hearing impairment learners. It cause the lack of their ability to arrange a right structure of sentence. Based upon the findings and conclusions, (1) The English teachers suggested to pay attention to the students’ condition when the teaching and learning process is being done, (2) The students should keep intention in learning English, and (3) The next researcher suggested to do research more complete about language acquisition and find the simple way to learn more vocabularies and hopefully makes the students can make a sentence in simple form or answer the short question in English fluently.